Aspects of complexity : minicourses in algorithmics, complexity, and computational algebra, mathematics workshop, Kaikoura, January 7-15, 2000 - Downey, R. G. (Rod G.); Hirschfeldt, Denis; Mathematics Workshop (NZMRI summer workshop) (De Gruyter Series in Logic and Its Applications, 2001)
The series is devoted to the publication of high-level monographs on all areas of mathematical logic and its applications. It is addressed to advanced students and research mathematicians, and may also serve as a guide for lectures and for seminars at the graduate level.